IMPACT OF COVID-19 PANDEMIC ON TEACHING AND LEARNING IN EDUCATIONAL STATUS OF SINDH. - Farzana Mallah1 , Kamlesh Kumar Ahuja 2 , Laraib Memon3 , Mumtaz Ali Chutto 4 , Vishamber Lal Rohra 5 , Waseem Raja Memon6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT The COVID-19 epidemic has disrupted educational systems in more than 200 nations and affected nearly 1.6 billion students, which is a record-breaking number. The closing of schools, foundations, and other educational institutions has had an effect on more than 94 percent of the world's pupils. As a result, everything in our life has changed considerably. Social isolation and constrictive developmental environments have profoundly disturbed traditional educational systems. Once a restriction has been eliminated, going back to school presents a test with numerous newly developed standard operating procedures. Numerous scientists who were working within the confines of the COVID-19 outbreak have shared their experiences with instructional learning in a number of ways. Only a few institutions, universities, and schools now provide one-on-one instruction. Losing the 2020 academic year or much more in the foreseeable future is a cause for concern. The development of the elective school system and the application of evaluation techniques are of highest importance. We now have a great opportunity to prepare to give advanced learning thanks to the COVID-19 pandemic. This essay seeks to present a complete examination of the COVID-19 epidemic's effects on online education and the learning of diverse papers, as well as to present future directions.